Measuring socioemotional wealth in family-owned and -managed firms: A validation and short form of the FIBER Scale. Issue 3 (September 2016) - Hauck, Jana; Suess-Reyes, Julia; Beck, Susanne; Prügl, Reinhard; Frank, Hermann
Highlights: Empirical validation of the FIBER scale for privately-held family firms. Theoretical validation of the FIBER scale. Short form with three dimensions called "REI scale". REI captures the core affective endowments a family may derive from its ownership. Abstract: Socioemotional wealth (SEW) is a key concept in family business research. The proposed FIBER scale as a direct and multidimensional measure of SEW is therefore a significant research achievement. We refined the scale by validating and thereby shortening it, using a sample of 216 family-owned and -managed firms with up to 500 employees in the German-speaking area. The validation reveals different degrees of validity across the five FIBER dimensions, resulting in a revised short form called the REI scale that comprises nine items that measure the core affective endowments a family may derive from controlling a firm. Based on our empirical validation, we discuss theoretical implications for the further development of a sound SEW measure.